Characterization and gas sensing properties of CuO synthesized by DC directly applying voltage - Klinbumrung A. (Elsevier, 2014)
CuO microstructure was successfully synthesized by 50 A and 3.6 V DC directly applying voltage. Crystalline structure was characterized by X-ray diffraction (XRD), morphology by scanning and transmission electron microscopy (SEM, TEM). The sample of the 15 min processing time has an irregular shape with diameter about several hundreds of nanometer. Fourier transform infrared (FTIR) spectroscopy, ultraviolet-visible (UV-vis) absorption spectroscopy and photoluminescence (PL) were used to determine vibrational modes and optical properties of the as-synthesized samples: 529 and 585 cm-1 vibrational modes, 3.95 eV band gap, and 402 nm emitting wavelength in violet region of CuO. X-ray photoelectron (XPS) spectroscopy was used to determine chemical composition, Cu(II)O, of the metal oxide surface. Gas sensing performance exposing to NH3 mixed with air at various working temperatures and NH3 concentrations of the as-synthesized CuO has the best response at the optimal working temperature of 250 °C: sensitivity of 56.6% exposed to 5275 ppm NH3. © 2014 Elsevier B.V. All rights reserved.